Enhancement of the anticonvulsant effect of the h3 histamine receptor blocker thioperamid against the use of pioglitazone - O. Yehorenko; M. Pervak; O. Poshyvak; A. Liashenko; L. Godlevsky (Kazimierz Wielki University, 2022)
The purpose of the study was to study the dynamics of foci of epileptic activity, which were reproduced in the cerebral cortex of kindled rats using the sodium salt of benzylpenicillin, under the conditions of individual and combined use of pioglitazone and thioperamid. Under conditions of acute observation in rats kindled with pentylenetetrazole repeated administration (30-35 mg/kg, i.p.), the influence of thioperamid (2,5 and 15,0 mg/kg, i.p.) and pioglitazone(50,0 and 200,0 mg/kg, i.p.) administrations upon penicillin-induced foci in the frontal cortex have been investigated. The data obtained showed that pioglitazone use in a previously ineffective dose (50.0 mg/kg, i.p.) but against the background of the administration of thioperamid (2.5 mg/kg, i.p.) was accompanied by the development of an anticonvulsant effect, which was expressed as inhibition of the amplitude and frequency of epileptic seizures potentials, as well as in reducing the life span of epileptic foci. A similar result indicates the possibility of restoration of sensitivity to the anticonvulsant effects of the studied drugs when they are used together in kindling provoked resistance to the action of antiepileptic drugs. Thus, the development of the antiseizure effect of thioperamid and pioglitazone, which were used in initially not effective dosages (2,5 and 50,0 mg/kg correspondently), have been described. This fact favors the synergy of the antiepileptic action of investigated compounds.